Enhancing Secondary School Students’ Achievement in Chemistry Using Collaborative Instructional Strategy - Nwafor, Stephen Chinedu; Okonkwo, Happiness C.; Onuigwe, Blessing Ukamaka (Journal of Digital Learning and Education, 2023)
The study explores the impact of a collaborative instructional strategy (CIS) on students' academic achievement in the Aguata Education Zone of Anambra State, Nigeria. The study also delved into the potential effect of gender on students' achievement in chemistry. The pre-test, post-test non-equivalent control group design was utilized in this quasi-experimental study. There were 2,328 senior secondary two Chemistry students in the population. A sample size of 101 Chemistry students (43 males and 58 females) was selected using the purposive sampling technique from two intact classes at two co-educational schools. Using Kendall's Coefficient of Concordance (w), the Chemistry Achievement Test (CAT) reliability index was calculated to be 0.94. While ANCOVA was used to test the hypotheses at 0.05 level of significance, mean and standard were used to answer the research questions. The findings of the study showed that CIS enhances students’ achievement in chemistry more effectively than the conventional strategy. Also, gender has no significant influence on students’ achievement in chemistry. It was recommended among others that educational stakeholders should hold conferences and seminars to train the teachers on how to use CIS in teaching and learning chemistry. Moreover, CIS should be used to ensure and enhance gender equity in both chemistry learning and other school subjects.